TATAKELOLA EDUWISATA CAGAR BUDAYA - Apriliani, Afmi; Tri Ramdani, Faisal; Fitriah, Maria; Wahyudin, Cecep; Jalaludin Assayuti, Muh; Alfin Zulfa, Agra; Munawaroh, Euis; Aryati, Siti (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Cultural heritage with the concept of Edutourism development is a special concern that must be supported by the Government Governance which is good for keeping local, tourism development and community economic improvement around tourism. This writing aims to find out the governance for the development of Edu Tourism in Tenjolaya Sub-District, Bogor Regency. The method used several steps including observation, preparation, Focus Group Discussion (FGD), counselling and training accompanied by a pre-test and post-test. The results of this service are generally that governance training activities are quite effective, namely that there is a significant increase in knowledge among participants with a percentage increase in knowledge and skills of 13.28%. This increase in knowledge has implications for increasing awareness of cultural heritage Edutourism management so that tourism awareness groups (pokdarwis) can be formed to govern tourism development in Tenjolaya Sub-District.